Small and combined tillage in crop rotation with different types of fallow - N. I. Vladykina (Аграрная наука Евро-Северо-Востока)
The possibility of replacing of moldboard treatments by resource-saving systems (light, combined) to obtain the productivity of crop rotation about 3.0 tons of grain units/ha and save of soil fertility was detected in long-term experiment at the sod-podzolic medium-eroded soil. In the three-factor experiment (9x6x2) types of fallow, tillage, fertilizer were studied in biologizing crop rotation: Fallow - Winter rye - Spring wheat - Barley + clover - Clover of the 1st year of use - Clover of the 2nd year of use - Winter rye - Barley - Oats. Saturation by grain crops is 66.7% which is important for many agricultural enterprises. Light and combined tillage systems at input of low dose of mineral fertilizers, biologization of crop rotation by organic fertilizer (manure, green manure), straw (an average of 27 t/ha) and sowing of clover (2 years of use) allowed to keep soil fertility and to obtain productivity at level 3.05 and 3.08 t grain units/ha. Manure input (60 t/ha) reduced the negative impact of light tillage and provided a positive NPK balance. At the crop rotation with green-manured fallow the light tillage is not conceded of moldboard and combined tillage on productivity (3.08-3.10 t grain units/ha), but worsened the agrochemical properties of the soil. Combined (light-moldboard) tillage system was more universal. It was effective in soil with a different fertility particularly (with a positive balance of NPK) on the background of manure. In the crop rotation with green-manured fallow (mustard) at straw input and low doses of mineral fertilizers (N180P120K120 for crop rotation) an energy efficiency ratio was 3.35; the flow of combustive and lubricating materials for autumn plowing was 10.1 l/ha; labor productivity in the autumn plowing for shift was 15.4 ha /7 hours. The content of mobile phosphorus and exchangeable potassium - 267 and 190 mg/kg, exchange acidity - 5.38, hydrolytic acidity and amount of exchangeable bases - 2.37 and 12.67 mg/100 g. The balance of humus - 5.51 t/ha. Weediness with annual and perennial weeds - 16.0 and 2.0 pc./m2. The development of root rots - 39.9 %.